Performance Evaluation of Cascaded and Reduced Switch Multilevel Inverter Using Modified Carrier Based PWM Technique (GUB Journal of Science and Engineering, 2020)
This paper proposes an improved harmonic distorted modified triangular carrier-based multicarrier pulse width modulation for generating the switching pulses of a multilevel inverter. This modified triangular wave consists of a triangular wave bearing a close resemblance to an ‘M’ shaped wave. The design of this carrier signal has been optimized to maintain a low level of total harmonic distortion (THD), while increasing the fundamental o/p voltage to ensure the effective DC voltage utilization. Moreover, this optimization reduces the switching losses and improve the efficiency of the power inverter. With the help of this carrier signal, High-frequency alternative phase opposition disposition pulse width modulation (APODPWM) is generated. This new control scheme has been applied to seven levels of conventional cascaded H-bridge with reduced switch multilevel inverter. The output is compared with conventional carrier-based APODPWM. The comparison is made in terms of THD, fundamental output voltages and inverter losses. To ensure quality performance, conventional carrier and modified carrier-based multicarrier PWM topologies are used for the Cascaded seven-level inverter with reduced switch seven-level inverter having a carrier frequency of 2 kHz and modulation index of 0.8-1.30. According to the simulation results, by using the proposed modulation scheme the THD and the switching loss were reduced by 9.64[%] and 4.2[%] respectively. Besides, the proposed modulation technique increases the fundamental output voltages. The total simulation process is done in MATLAB Simulink environment.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 6(1), Dec 2019 P 12-19